Monitoring the freshness of fish: development of a qPCR method applied to MAP chilled whiting. (4th August 2015) - Dehaut, Alexandre; Krzewinski, Frédéric; Grard, Thierry; Chollet, Marlène; Jacques, Philippe; Brisabois, Anne; Duflos, Guillaume
Abstract: BACKGROUND: Monitoring of early stages of freshness decay is a major issue for the fishery industry to guarantee the best quality for this highly perishable food matrix. Numerous techniques have been developed, but most of them have the disadvantage of being reliable only either in the last stages of fish freshness or for the analysis of whole fish. This study describes the development of a qPCR method targeting the torA gene harboured by fish spoilage microorganisms. torA encodes an enzyme that leads to the production of trimethylamine responsible for the characteristic spoiled‐fish odour. RESULTS: A degenerate primer pair was designed. It amplified torA gene of both Vibrio and Photobacterium with good efficiencies on 7‐log DNA dilutions. The primer pair was used during a shelf‐life monitoring study achieved on modified atmosphere packed, chilled, whiting ( Merlangius merlangus ) fillets. The qPCR approach allows the detection of an increase of torA copies throughout the storage of fillets in correlation with the evolution of both total volatile basic nitrogen (−0.86) and trimethylamine concentrations (−0.81), known as spoilage markers. CONCLUSION: This study described a very promising, sensitive, reliable, time‐effective, technique in the field of freshness characterisation of processed fish. © 2015 Society of Chemical Industry